INVESTIGATION OF AUTOMATIC REACTIVE POWER COMPENSATION IN POWER SUPPLY SYSTEMS (International conference on multidisciplinary science, 2026)
At present, improving the efficiency of electricity use at industrial enterprises is one of the most important tasks. In production processes, the widespread use of asynchronous motors, transformers, welding units, compressors, and other inductive electrical consumers causes a significant increase in reactive power consumption. The growth of reactive power leads to an increase in current in electrical networks, higher active power losses, voltage drop, overloading of network elements, and deterioration of the power factor. As a result, the technical condition of the power supply system worsens, the risk of emergency operation increases, and energy use becomes economically inefficient.In many enterprises, capacitor banks are used to reduce reactive power consumption. However, under conditions where the load changes during the day, within shifts, or according to technological cycles, simple uncontrolled capacitor banks do not always ensure high efficiency. In some cases, compensation is insufficient, while in others overcompensation occurs. This may cause voltage rise above permissible limits, overheating of equipment, and a reduction in the service life of capacitor installations. Therefore, the issue of automatically controlling reactive power in accordance with real operating conditions is highly relevant.